Does the G7/G8 promote trade? - Volker Nitsch (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2006)
The Group of Eight (G8) is an unofficial forum of the heads of state of the eight leading industrialized countries. In this paper, I examine the effect of the G8 (and its predecessor, the G7) on international trade. I use a gravity model of trade; the panel data set covers bilateral trade between 175 countries from 1948 through 1999. I find that membership in the G7/G8 is consistently associated with a strong positive effect on trade.
Keywords: F13; F15; 330; institution; organization; agreement; international; multilateral; summit; Gravitationsmodell; Außenhandelsförderung; Internationale Organisation; Internationale wirtschaftspolitische Koordination; G-8-Staaten